Asset-Based Community Development in Vocational Schools Through Appreciative Inquiry (AI) and the BAGJA Model - Raindra Anggraeni Rosmalinda; Sobari Sobari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study examines the implementation of asset-based community development at SMK 2 LPPM RI Majalaya using qualitative methods through observation, interviews, and documentation. The findings reveal a significant gap between the availability of assets, including physical assets (workshops, laboratories), movable assets, and human assets (educators and students), and their collective mobilisation, attributed to the absence of a collaborative framework or